Design of Inventory Management and Cashier System - Rozaq Isnaini Nugraha; Supriyanto; Yane Puspito Sari (ProBisnis : Jurnal Manajemen, 2023)
The rapid development of technology at this time is needed by various fields, which are used to support and manage the assets of both large companies and small companies. The utilization of computer-based technology is important to overcome the problems of companies and business competitors who are increasingly competitive. The information system developed includes monitoring the stock of goods, buying and selling processes, and reporting on buying and selling of goods. The inventory system development method will use the RAD (Rapid Application Development), With the availability of this inventory system design, it is hoped that HR Ambar Batik can more easily manage inventory, and obtain sales information more quickly and accurately. The output target of this research is the availability of an inventory management system for management at HR Ambar Batik.